2006
DOI: 10.1029/2005ja011450
|View full text |Cite
|
Sign up to set email alerts
|

Computing magnetospheric mass density from field line resonances in a realistic magnetic field geometry

Abstract: [1] Ultra-low-frequency (ULF) field line resonances can be used to infer the mass density along magnetospheric magnetic field lines. By specifying how mass density is distributed along the magnetic field (usually a power law as a function of distance from the Earth) and a dipole magnetic field geometry, the MHD standing wave equation can be analytically solved and mass density inferred from observed field line eigenfrequencies. However, the geometry of the Earth's magnetic field can deviate significantly from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 30 publications
1
37
1
Order By: Relevance
“…At latitudes higher than those examined in this paper (L > 4), we expect from previous studies [Warner and Orr, 1979;Singer et al, 1981;Berube et al, 2006] that the effects of the external sources can become more relevant than those investigated here. In particular, Berube et al [2006], using the T01 magnetic field model [Tsyganenko, 2002], found that these effects are significant even at relatively low L-shells (L ≅ 3) for disturbed magnetospheric conditions (Dst <~À50 nT).…”
Section: Summary and Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…At latitudes higher than those examined in this paper (L > 4), we expect from previous studies [Warner and Orr, 1979;Singer et al, 1981;Berube et al, 2006] that the effects of the external sources can become more relevant than those investigated here. In particular, Berube et al [2006], using the T01 magnetic field model [Tsyganenko, 2002], found that these effects are significant even at relatively low L-shells (L ≅ 3) for disturbed magnetospheric conditions (Dst <~À50 nT).…”
Section: Summary and Discussionmentioning
confidence: 59%
“…In particular, Berube et al [2006], using the T01 magnetic field model [Tsyganenko, 2002], found that these effects are significant even at relatively low L-shells (L ≅ 3) for disturbed magnetospheric conditions (Dst <~À50 nT). On the other hand, for average solar wind/magnetospheric conditions, a preliminary analysis conducted by Vellante et al [2013] shows that mass densities computed using the IGRF model result to be only moderately overestimated with respect to those computed using the T01 model (less than 10% for L ≤ 3, and at most 20% at L = 4).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of the FLR technique include the choice of fieldaligned density and magnetic field models (Berube et al 2006;Takahashi et al 2006;Vellante & Föster 2006), experimental uncertainty in determining resonant frequencies, and the lack of FLR observations at night.…”
Section: Introductionmentioning
confidence: 99%
“…Singer et al (1981) investigated the structure of Alfvén waves in a realistic (nondipolar) field and provided tools for understanding how ULF wave frequencies depend on the structure of the background magnetic field. The work was formulated so that it can be applied to any field model, and is being used today in work relating resonant frequencies to mass content of plasmaspheric flux tubes (Berube et al 2006).…”
Section: Professor At Lastmentioning
confidence: 99%